Influence of Boron Adding on the Acoustic Materials Signature Curves for Computing of Surface Acoustic Wave Velocities of Ti64 Alloys - Al-Sayad, Y.; Hadjoub, Z.; Doghmane, A. (Металлофизика и новейшие технологии, 2018)
The effect of Boron admixture with five different concentrations x = 0.0, 0.04, 0.09, 0.30 and 0.55% wt. B on elastic properties of Ti–6Al–4V alloy is investigated. The values of velocities of propagating surface acoustic wave as well as bulk wave for additional structures are deduced. As found, with the increasing of Boron content in Ti–6Al–4V alloy, its acoustic material signature (Young’s modulus E, shear modulus G, bulk modulus B), longitudinal velocities, and shear velocities increase from 113 to 126 GPa, from 42.5 to 47.4 GPa, from 110.8 to 123.5 GPa, from 6148 to 6492 m/s, from 3097 to 3171 m/s, respectively. Using angular spectrum model, we calculate the reflectance function and the acoustic materials signature of Ti–6Al–4V–xB, which show an oscillatory behaviour. The spectral treatment of these signatures provides the exact definition of Rayleigh wave velocity.